Fetal programming of gene expression in growth-restricted rats depends on the cause of low birth weight - Nuesken, Kai-Dietrich; Schneider, Holm; Plank, Christian Georg; Trollmann, Regina; Nuesken, Eva; Rascher, Wolfgang; Doetsch, Joerg (Endocrinology, 2011)
Low birth weight and intrauterine growth restriction (IUGR) can be caused by numerous different conditions. In many experimental settings, however, these different causes are not accounted for. This study aimed at comparing the impact of two frequent causes of IUGR (low utero-placental blood flow vs. malnutrition) on fetal programming of gene expression. We studied offspring of dams treated by uterine artery ligation or sham operation compared with untreated controls and offspring of dams that were fed either a low protein or normal protein diet. After Cesarean section at term, placental and fetal hepatic expression of key "metabolic" and "vasoregulative" genes was investigated by quantitative RT-PCR. Ligation neonates showed IUGR, reduced expression of placental leptin, placental and hepatic IGF-I, hepatic inducible nitric oxide synthase, and increased expression of placental IGF binding protein 1, hepatic IGF-II receptor and erythropoietin (EPO).Low protein offspring also showed IUGR but increased expression of placental leptin; IGF-I; placental and hepatic inducible nitric oxide synthase; hepatic insulin, IGF-I, and IGF-II receptors; and reduced expression of placental IGF binding protein 1, IGF-II, leptin-receptor type A, placental and hepatic leptin receptor type B, and EPO. Expression was independent of sex, birth weight, fetal intrauterine position, and EPO expression. In conclusion, the impact of IUGR on fetal and placental gene expression depends on the cause of low birth weight. Therefore, morbidity after IUGR should be analyzed referring to its pathophysiological cause rather than referring to low birth weight itself. Fetal hypoxia as estimated by hepatic EPO expression does not seem to be a key regulator of transcriptional activity in our models. Copyright © 2011 by The Endocrine Society.
CRIS-Team Scopus Importer:2020-07-01